Electrical duality design for the radon-222 decay chain. (April 2020) - Ahmadi, Mohammad; Soltani-Nabipour, Jamshid; Khorshidi, Abdollah; Negarestani, Ali; Taheri, Fariba
Abstract: In this study, electrical-nuclear reduplication was modeled by the similarity of decay equations with corresponding circuit equations to find an equivalent circuit for decay chain of radon-222. Each step was implemented along with the corresponding geometric diagram through a reduplication process in the decay chain. Through the relevant-circuit determination of three-phase equations into nine-phase equations of the decay, the curves derived from interactions were temporally examined as a capacitor current into the relevant capacitance ratio. The acquired waveforms demonstrated that the defined ratio is equal to the activity of the corresponding decay into the equivalent circuit. If the mother nuclei were neglected up to lead-210 decay, the obtained curves for daughter activity met the desired criteria by 0.000095 fg (femto.gram). Subsequently, when the mother nuclei were considered to be the initial nuclei, the reduplication occurred between the number of mother nuclei and the initial voltage of the capacitor. If the radiation causes the daughter wave to overtake the mother wave (cross-talk) and the detector is of the daughter-meter type, a pulse height defect is formed which is not desired. The nature of output response waveform, along with cross-talk and accumulation effects, determines which type of detector— mother or daughter meter— is suitable for reading. Correlating nuclear decay equations with relevant electric circuit equation may provide a facile method to interpret any chain data. Highlights: A concept was proposed in nuclear decay issue by relevant circuit equation similarity. Equivalent electrical circuit was designed for Rn-222 decay chain by 3 into 9-phase equations. Obtained curves from interactions were temporally inspected as current into capacitance ratio. Activity of the corresponding decay was equal to the equivalent circuit. Reduplication occurred between number of mother nuclei and initial voltage of capacitor.